The Way Back Home - Jeffers, Oliver (London HarperCollinsPublishers, 2007)
Once there was a boy who, one day, found himself stuck on the moon, and he was not alone.
Include Color Illustration
Keywords: Space flight -- Cooperativeness -- Extraterrestrial beings